Program Sosialisasi dan Pelatihan Penggunaan Sistem Informasi Posyandu: SIMBAT (Sistem InforMasi BalitA Sehat Terpadu) - Widiyanto, Wahyu Wijaya; Igiany, Prita Devy; Sari, Arum Astika (Jurnal Abdi Mas Adzkia, 2023)
In every organization, including Posyandu (Integrated Service Post) which is a public health institution based on community empowerment, information systems have a key role in providing accurate and timely information for reporting and decision making, in line with the Ministry of Health's regulations regarding health transformation as outlined in PMK No.24 of 2022. However, the effectiveness of the SIMBAT Posyandu Information System is hampered by the lack of ability of a number of posyandu cadres to use information and communication technology (ICT). To overcome this problem, this program was implemented which aims to improve the ability of Posyandu cadres in managing health information, especially in registration, recording and reporting, through socialization of the use of the Web-Based Posyandu Information System. Methods for implementing this socialization program include coordination with partners, needs analysis, training planning, preparation of training tools and materials, and implementation of training. The result of this activity is the ability of posyandu cadres to use information and communication technology, including the SIMBAT application based on pretest and posttest results, initially 40% after training became 80%.